Marginalisasi Perempuan Dalam Dunia Pendidikan - Astutiningsih, Sri Eka (Sunan Kalijaga State Islamic University & The Asia Foundation, 2008)
Women have experienced gender inequalities in many aspects of human life, including in education. Education which is ideally accessible equally for everyone, in fact, has been discriminative against women. There are many factors that bring about women marginalization in the field of education including: 1) a strong patriarchal culture; 2) gender biased curriculum, text books, and teaching and learning process; 3) curriculum evaluator, educational advisers, and teachers who does not have gender sensitivity. The most fundamental factor has been male dominated and oriented society. In order to develop more gender equal educational system, therefore, there is a need to restructure the gender biased,curriculum and develop an inclusive gender teaching and learning process. In the process of teaching and learning teachers have to encourage both male and female students to have critical knowledge, behavior, and awareness, emphasize the importance of gender equality, and avoid using gender biased language. There are three significant aspects included in the development of gender equality in curriculum: teacher, student, and the produced knowledge. Gender inequality that results in women marginalization in education, thus, should be eliminated. AU have to work hard hand in hand to be able to create gender equality in education.